O governo do PT e a Alca: política externa e pragmatismo - Oliveira, Amâncio Jorge de (Estudos Avançados, 2003)
The main purpose of this article is to analyse the position of Brazil's Work Party about the Free Trade Area of the Americas (FTTA). The paper intend to show that the party's position changed between elections run and the beginning of negotiation process because constraints of the process. The paper intend also to foster comprehension toward incentives, positives and negatives, about the Brazilian decision take of the FTAA. Incentives, by the way, little focused in Brazil's debate about this theme.